Implementation of the PBL Model to Improve Learning Outcomes in Establishing the Experience of Elementary Students - Afdhilah, Yusroul; Budiono; Sucipto (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The learning outcomes of class VI students in the Indonesian language subject matter of experience framing are still low, which is indicated by the fact that many students have not reached the minimum KKM. The low learning outcomes are caused by the learning process, which has not increased students’ learning motivation. This classroom action research aims to improve the learning of class VI students by implementing the PBL model on student learning outcomes. This research involved 20 grade VI students at SDN Junrejo 2 Batu who were positioned as research subjects. The instruments used in this research are observation and tests. The results of this study indicate an increase in the learning outcomes of Indonesian language students in class VI at SDN Junrejo 02 Batu in constructing experiences after using the PBL model. This can be seen from comparing the mastery of student learning outcomes in pre-cycle conditions of 25%, in cycle I increased to 30% and in cycle II increased to 85% with KKM 70. So it can be concluded that the PBL model can improve student learning outcomes in the Indonesian language subject assembling the experiences of class VI SD